Crisis in the infancy: what the children think, feel and say, on the separation of the parents? - Cifuentes Neumann, Oriana Anet; Pontificia Universidad Catolica de Valparaiso (Pontificia Universidad Javeriana, 2011)
The article presents the qualitative study of narratives of children from 9 to 12 years old, about the separation (divorce) of their parents. The sample consisted of 12 children (boys/girls), middle class and the analysis of the data was done according the procedures of the “Grounded Theory”. The purpose of the study is to reveal the experience of Chilean children about their parents divorce and the meaning of that experience in their lives now. The study results indicate that the parental separation (divorce) is a crisis for the child, who represents it as the lost of the nuclear family. This experience affects his behavioral and socioemocional performance generating mood changes that are evident in the school and social area. After two or three years, the child manage to take some distance from the experience and evaluate it from a new perspective. Thus some of them reframing the crisis considering favorable elements identified in the present.